Shadow of night - Harkness, Deborah E., 1965- (New York : Viking, 2012)
Oxford scholar and reluctant witch Diana Bishop and vampire geneticist Matthew Clairmont are in Elizabethan London, where Diana seeks a magical tutor and Matthew confronts elements from his past; at the same time the mystery of Ashmole 782 deepens.
Series title from book jacket.
Keywords: Bishop, Diana (Fictitious character) -- Fiction; Clairmont, Matthew (Fictitious character) -- Fiction; Witches -- Fiction; Vampires -- Fiction; Manuscripts -- Fiction; Magic -- Fiction; Time travel -- Fiction; London (England) -- Fiction; Great Britain -- History -- Elizabeth, 1558-1603 -- Fiction; Fantasy fiction; Historical fiction; Paranormal romance stories